Testing for cystic fibrosis using allelic association. Issue 7 (July 1989) - Ivinson, A J; Read, A P; Harris, R; Super, M; Schwarz, M; Clayton Smith, J; Elles, R
Abstract : A particular haplotype defined by probes XV2c, KM19, and CS.7 at the D7S23 locus was found on 90% of chromosomes which carry cystic fibrosis (CF), but on only 11% of normal chromosomes in a UK sample of CF carriers. We show how such data can be used to calculate carrier risks for people with and without a family history of CF, and give examples of clinical applications. For parents or sibs of dead CF patients, phase and genotypes can often be assigned with only 1 to 2% error. However, this method is not suitable for prenatal testing where there is no history of CF; for couples with no family history, no fetus can be shown to be at more than 2% risk of being affected.